TABOO WORDS FOUND IN NOVEL ENTITLED “RONGGENG DUKUH PARUK” BY AHMAD TOHARI - ANGGRAINI, DINI LUSIDA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Taboo Words, Novel, Ronggeng Dukuh Paruk. Taboo word is one of language phenomena that exist in society although these words are forbidden to be spoken. Taboo words can be found not only in everyday conversation, but also in literary works such as novels. This study examines the taboo words that exist in the novel entitled Ronggeng Dukuh Paruk.Ronggeng Dukuh Paruk novel written by Ahmad Tohari tells about the life of aronggeng, and the culture of Dukuh Paruk. In this study, the writer analyzed twoproblems namely; (1) The types of taboo words found in novel entitled Ronggeng Dukuh Paruk, and (2) The purposes of taboo words found in novel entitled Ronggeng Dukuh Paruk.In this study, the writer uses the theory from Wijana and Rohmadi (2013)to answer the first problem of the study about the types of taboo words. Besides, the writer also uses the theory from Liedlich (1973) to answer the second problem of the study about the purposes of taboo words found in the novel. This study used qualitative methods and document analysis.In this study, the writer found four types of taboo words, namely situation (25 words), animals (41 words), spirits (one word), and professions (19 words). The writer also found the six purposes of taboo words in the novel. The purposesof the use of taboo in this novel are to create attention, to discredit, to provokeviolent confrontation, to show endearment, to create strong personal identification, and to provide catharsis.In the process of research, the writer concludes that the mostly kind of taboo word used in Ronggeng Dukuh Paruk novel is taboo word using animal. It is because the influence of the environment, which is still attached to the life of ‘Dukuh Paruk’ people, that is still very natural. People in ‘Dukuh Paruk’ always connect natural events with the events that will happen. Therefore, they curse the interlocutor by using the names of animal that they think are similar to theattitude, behavior, or the look of their interlocutors.The writer suggests for the next researchers who will conduct research on taboo word to use other theories. The writer also suggest the next researchers to analyze taboo words not only in novel or movie, but also in other objects such asdaily conversation, poem, or talk show in television.